Where Is the Gender in Gendered Language? - Thomson, Rob; Murachver, Tamar; Green, James (Psychological Science, 2001)
The purpose of these studies was to examine how women and men react and accommodate to gender-preferential language in e-mail messages. In Experiment 1, participants wrote messages to two assigned “netpals.” These netpals were actually one of the experimenters. For each participant, one netpal used female-preferential language and the other used male-preferential language. Analyses revealed that the netpals' language style, and not the participants' gender, predicted the language used by participants in their e-mail replies. Female and male participants used the gender-preferential language that matched the language used by their netpals. In Experiment 2, the gender labels and language styles of netpals were independently manipulated. As before, linguistic style had the greatest impact on participants' language use. These results have implications for how people think about gendered behavior, and highlight how gendered language is constructed in social interaction.